Dental caries in the primary dentition of a Colombian population according to the ICDAS criteria - Alexandra Saldarriaga Cadavid; Clara María Arango Lince; Marisela Cossio Jaramillo (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This paper describes the results of a cross-sectional study conducted with a randomized sample of 447 low-income children between 2.5 and 4 years of age selected from the files of a health institution in Medellin, Colombia. The patients were examined in 2007 using the modified criteria of the International Caries Detection and Assessment System (ICDAS); the first caries code was not used. Clinical examination was carried out by three examiners previously trained in the ICDAS. The inter-examiner agreement was rated as good (kappa 0.73 - 0.82). The prevalence of untreated caries was 74.7% (335) with a mean of 9.7 ± 9.4 affected surfaces. The prevalence of caries (treated and untreated) was 74.9% (335). The mean dmf-s was 7.6 ± 9.7. The prevalence of non-cavitated lesions on at least one tooth surface was 73.4%. Cavitated lesions were more frequent on smooth surfaces than on occlusal surfaces (respectively 64.7% and 46.8%; p value < 0.001). Only 25.1% (112.5) of the children had no clinical signs of caries according to the ICDAS criteria. It was concluded that dental caries is a highly prevalent condition in this Colombian population, the main contributor being non-cavitated lesions. There was an association between caries and oral hygiene practices, such as the amount of toothpaste used, and also between caries and the occurrence of a previous dental visit (p value < 0.00). Eating habits constituted no statistically significant association.